Semantic Analysis of the Poem “Derai - Derai Cemara” by Chairil Anwar - Bonita Manullang; Rosmawaty Harahap (Journal of Aceh Studies, 2025)
Poetry is a literary genre that is of interest to various groups and ages of society. Some people prefer to write poetry rather than just reading it. Language poetry is usually unregulated and free. Poetry sometimes has a lot of figurative language that is difficult to understand. The aim of this research is to explain the meaning contained in poetry using semantic analysis which focuses on lexical meaning, grammatical meaning, referential meaning and figurative meaning. Qualitative descriptive methodology was used in this research. Two data collection methods were used in this research: the library method collected data from various written sources, including literary works; the observation method involves reading the text thoroughly and critically; and this research is included in the type of library research, which combines data from various literature. Not only books, but also documents, magazines, journals and newspapers can be studied. Analysis shows that many of the vocabulary used in the poem Derai-Derai Cemara by Chairil Anwar have lexical, grammatical, referential and figurative meanings. Chairil Anwar's poem "Derai-Derai Cemara" talks about despair and resignation caused by an unreasonable life.